Pengaruh Penggunaan Gadget Terhadap Interaksi Sosial Anak Usia Dini : Literature Review - Anugrah Perdana; Yusuf Bachtiar; Dini Nur Alpiah (JURNAL ILMIAH NUSANTARA, 2024)
Social interaction in early childhood is an important aspect in their social-emotional development. Social interaction in early childhood influences their holistic development. Gadgets or technological devices such as smartphones and tablets have become an integral part of many people's daily lives in this modern era. However, excessive use of gadgets can affect an individual's social interactions. This research examines the influence of gadget use on early childhood social interactions. This research uses the PICO method in the Google Scholar database. There were 5 journals that met the criteria and showed the results of the influence of gadget use on the social interactions of early childhood.